Industrial ergonomics ([Victoria, Australia] : Vocam Worldwide Publishing, 2001)
Learn to identify ergonomic problems in the workplace and find practical solutions. Topics covered include: Common injuries; Posture; Back & neck; Arms & shoulders; Hands & wrists; Legs & feet; Repetitive actions; Excessive force; Weight & nature of objects; Ergonomics at home
Title from title screen
VCD format
Keywords: Human engineering; Human -- Machine systems